4y-(2y-1)=7

Simple and best practice solution for 4y-(2y-1)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-(2y-1)=7 equation:


Simplifying
4y + -1(2y + -1) = 7

Reorder the terms:
4y + -1(-1 + 2y) = 7
4y + (-1 * -1 + 2y * -1) = 7
4y + (1 + -2y) = 7

Reorder the terms:
1 + 4y + -2y = 7

Combine like terms: 4y + -2y = 2y
1 + 2y = 7

Solving
1 + 2y = 7

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 2y = 7 + -1

Combine like terms: 1 + -1 = 0
0 + 2y = 7 + -1
2y = 7 + -1

Combine like terms: 7 + -1 = 6
2y = 6

Divide each side by '2'.
y = 3

Simplifying
y = 3

See similar equations:

| x^2+2x-143=0 | | 9y-14=26+13y | | 3=x+3-x | | 5-(8-c)=0 | | 7x=109.2 | | y=12x+420 | | 260=k(1300) | | 2x=12.25 | | 48=k(6) | | 8m-(6m-3)=9 | | 3n-(5n+2)=8 | | 12h-18=12h-18 | | 6(y+2)-2y=15 | | 2x+19=1x-80 | | 6-(3x-3)-[2(-4x-1)]=(-3x+2) | | 12-2x=7x-15 | | 5n-9=2n+3 | | -(-4x+6-8)= | | -f(x-2)g=(x^2-3+2) | | 18=k(3) | | -24x+4x^2=0 | | (3x+72)(x-1)= | | 5x=x+26 | | 12h-18=(4h-6) | | 12x-60=0 | | 6(4y-1)=5 | | 2(x+5)=8 | | 3-n=33 | | x-6=(x-4)1/2 | | y=1.5(1) | | V=dt | | 4x^2-8=20 |

Equations solver categories